Recurrent Pancreatitis Secondary to Common Channel Volvulus through Petersen’s Space Defect in a Patient with Roux-En-Y Bypass (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Gastroenterology; Case Report